2022
DOI: 10.1113/jp282528
|View full text |Cite
|
Sign up to set email alerts
|

Maternal sleep behaviours preceding fetal heart rate events on cardiotocography

Abstract: Hospital for Women. She recently completed her PhD looking at the prevalence and impact of sleep-disordered breathing in hypertensive disorders of pregnancy, and aspires to extend her research programme into sleep behaviours and sleep disorders during pregnancy and the role they play in maternal and fetal wellbeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…Whilst the healthy placenta and fetus may tolerate the effects of up to a 50% reduction in uterine arterial blood flow [ 60 ], this is less likely to be the case in pregnancies complicated by maternal hypertensive disease and/or fetal growth restriction. In an overnight sleep study of 116 participants synchronizing maternal position with fetal heart rate events, maternal position change and especially in the supine position was significantly more likely to be associated with adverse FHR events in women with FGR and/or a hypertensive disorder compared with uncomplicated pregnancies ( p = 0.006) [ 61 ], providing further evidence that the fetus was responding to hypoxia induced by position change.…”
Section: Review Of Physiological Assessments Of Maternal and Fetal Im...mentioning
confidence: 99%
“…Whilst the healthy placenta and fetus may tolerate the effects of up to a 50% reduction in uterine arterial blood flow [ 60 ], this is less likely to be the case in pregnancies complicated by maternal hypertensive disease and/or fetal growth restriction. In an overnight sleep study of 116 participants synchronizing maternal position with fetal heart rate events, maternal position change and especially in the supine position was significantly more likely to be associated with adverse FHR events in women with FGR and/or a hypertensive disorder compared with uncomplicated pregnancies ( p = 0.006) [ 61 ], providing further evidence that the fetus was responding to hypoxia induced by position change.…”
Section: Review Of Physiological Assessments Of Maternal and Fetal Im...mentioning
confidence: 99%
“…Moreover, maternal sleep position was associated with changes in fetal behavioral state and FHR variability (Stone et al, 2017). A study of CTG with maternal polysomnography in late pregnancy reported that nocturnal FHR decelerations and prolonged reduction in FHRV were more likely in pregnancies complicated by hypertension and/or FGR, and these changes were associated with maternal sleep position (Wilson et al, 2022). This suggests that an adverse event (e.g.…”
Section: Antenatal Fetal Heart Rate and Heart Rate Variability Markersmentioning
confidence: 99%